Indications for and efficacy of splenectomy for haematological disorders. Issue 6 (21st February 2013) - Bickenbach, K. A.; Gonen, M.; Labow, D. M.; Strong, V.; Heaney, M. L.; Zelenetz, A. D.; Coit, D. G.
<x xml:space="preserve">Abstract</x> Not without risks